Terahertz Technology and Its Applications - Peña, Victor Pacheco (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The Terahertz frequency range (0.1 - 10)THz has demonstrated to provide many opportunities in prominent research fields such as high-speed communications, biomedicine, sensing, and imaging. This spectral range, lying between electronics and photonics, has been historically known as "terahertz gap" because of the lack of experimental as well as fabrication technologies. However, many efforts are now being carried out worldwide in order improve technology working at this frequency range. This book represents a mechanism to highlight some of the work being done within this range of the electromagnetic spectrum. The topics covered include non-destructive testing, teraherz imaging and sensing, among others.